2013
DOI: 10.5539/ijbm.v8n22p76
|View full text |Cite
|
Sign up to set email alerts
|

Structural Co-Alignment Influence on SMEs Performance

Abstract: Organizational structure is a determining factor in organizational performance. Although structural contingency theory in the field of organizational studies and the structural co-alignment theory in the field of strategic management, have provided points of reference to comprehend the phenomenon of organizational performance, there are still gaps to be filled and empirical validation is required, above all in the influences on performance and especially in relation to Colombian Small and Medium Enterprises (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 85 publications
0
6
0
3
Order By: Relevance
“…Companies have to make decisions about organizational design in an increasingly complex and unpredictable environment. They seek to align the organizational culture, organizational structure, and business strategy to face these environmental forces and thus ensure their survival, durability, and greater performance (Ánzola, Marín-Idárraga, & Cuartas, 2017;Burton & Obel, 2004;Marín-Idárraga & Cuartas-Marín, 2013).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Companies have to make decisions about organizational design in an increasingly complex and unpredictable environment. They seek to align the organizational culture, organizational structure, and business strategy to face these environmental forces and thus ensure their survival, durability, and greater performance (Ánzola, Marín-Idárraga, & Cuartas, 2017;Burton & Obel, 2004;Marín-Idárraga & Cuartas-Marín, 2013).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…De esta forma, aunque existen diferentes taxonomías acerca de las variables que componen la estructura organizacional, por ejemplo las definidas inicialmente por el grupo Aston de Inglaterra (Pugh, Hickson, Hinnings y Turner, 1968;Pugh et al, 1963), el factor común a ellas es la consideración de la diferenciación, la formalización y la descentralización como las más determinantes (Dalton, Todor, Spendolini, Fielding y Porter, 1980;Marín-Idárraga y Cuartas-Marín, 2013).…”
Section: Estructura Organizacionalunclassified
“…Este estudio contribuye en tal dirección, al proporcionar evidencia empírica que suma a los estudios acerca de las implicaciones que tienen las variables estructurales en el ajuste organizacional y el desempeño (Donaldson, 1987;Drazin y van de Ven, 1985;Marín-Idárraga, 2012;Marín-Idárraga y Cuartas-Marín, 2013;Venkatraman y Camillus, 1984). En este sentido, la conclusión medular que queda para las IPS es que la conformación de relaciones inter-organizacionales con otras entidades similares se ve mejor influenciada por una estructura descentralizada, y que la satisfacción en ese acuerdo cooperativo (y su posibilidad de continuidad) depende en buena medida del intercambio de información y de la correspondencia en propósitos y valores.…”
Section: Conclusiones E Implicacionesunclassified
See 1 more Smart Citation
“…Studies of Rosenbusch, Brinckmann, and Bausch [1]; Marí n-Idá rraga, Hurtado, and Cabello [2] have shown that product innovation is a value-addition activity for enterprises, and Keupp, Palmié , and Gassmann [3] noted that it has been an approach for realizing competitive advantage. Though some in some studies, it was theoretically revealed that product innovation is a factor that determine enterprise survival [4], [5], [6]. Rosenbusch et al [1] noted that empirical results of many studies are contradictory, especially those that treated small and medium-sized enterprises (SMEs).Some empirical researches reveal a positive and significant nexus between product innovation and enterprise survival [6], [7], while other researches reveals negative nexus [8], [9].…”
Section: Introductionmentioning
confidence: 99%